KABA GOMBANG PATUANAN: AN ORAL LITERARY WORK OF MINANGKABAU PESISIR SELATAN REGENCY, WEST SUMATRA - Krisna, Eva; Kuta Ratna, I Nyoman; Cika, I Wayan; Weda Kusuma, I Nyoman (e-Journal of Linguistics; Vol. 3. Juli 2009 No. 2, 2009)
Kaba Gombang Patuana (abbreviated to KGP) is a Minang literary genre whichis orally presented in the form of songs. Therefore, it is known as an intonational prose.As a piece of oral literary work, KGP needs a medium of presentation. The mediumneeded is in the form of a performance known as Pertunjukan Kak Oai (PKO), whichexists at Kenagarian Air Haji, Pesisir Selatan Regency, West Sumatra. Kaba GambangPatuanan tells about the socio cultural life of the community of Pesisir Selatan Regencyusing the local variety of Minangkabau language. The availability of the texts of KGP,the performance of PKO, and the collective community possessing such a literary workshows that the phenomenon of what is written and spoken about oral literary work isdifferent from the phenomenon of what is written and spoken about written literary work.Oral literary work cannot be approached from literary discipline only, but linguisticapproach and anthropological approach are also needed.The morphology of KGP is made up of stem of the story ‘batang curito’, branchof the story ‘dahan curito’ , and twig of the story ‘rantiang curito’. The batang curito(the stem of the story) is the text of GPP as a whole. The ‘Dahan Curito’ (the branch ofthe story) serves as the episodes of the story and the Ranting Curito serves as the parts ofthe episode. The functions performed by KGP are: (1) as a medium for conveying what isexpected from a king; (2) as a medium for conveying Minang tradition; (3) as a mediumfor conveying oceanic knowledge; (4) as a medium for conveying nation-lovingenthusiasm ‘chauvinism’ ; (5) as a medium for conveying henotheism towards ancestors.
Keywords: literary genre, literary work, and local variety.